Enhancing the Lifetime of Underwater Wireless Sensor Networks - Kumar, Yashwanth KS; SA, Rajshekar (International Journal of Computer Sciences and Engineering, 2025)
There is no denial in the fact that a huge portion of the underwater world whether its seas, oceans or rivers not been explored yet. In recent year, researchers are finding ways to explore and study the underwater resources. Underwater wireless sensor networks, developed for gathering information from the undersea environment. Due to the undersea environment features, enhancing the network lifetime is a significant object. In this paper a 3D node deployment strategy, an algorithm for relay node setting in underwater wireless sensor network (UWSN) with enhancing performance of routing in underwater wireless sensor network has presented. The 3D node deployment strategy targets 3D UWSN and not only improves the routing protocol performance in terms of end-to-end delay and energy consumption but also provides reliability in data transmission and increases network lifetime. For fixing a relay node in an appropriate place, an algorithm which is named Relay Node Setting Algorithm (RNSA) that works in a 3D UWSN has presented. The proposed algorithm for improving the network lifetime, upon entry the relay node, finds an appropriate place for it. Routing protocol performs route discovery and route maintenance phase which tries to minimize the network data and packet collision.